Cytoskeleton and nuclear lamina affection in recessive osteogenesis imperfecta: A functional proteomics perspective - Gagliardi, Assunta (J Proteomics, 2017)
Osteogenesis imperfecta (OI) is a collagen-related disorder associated to dominant, recessive or X-linked transmission, mainly caused by mutations in type I collagen genes or in genes involved in type I collagen metabolism. Among the recessive forms, OI types VII, VIII, and IX are due to mutations in CRTAP, P3H1, and PPIB genes, respectively. They code for the three components of the endoplasmic reticulum complex that catalyzes 3-hydroxylation of type I collagen α1Pro986. Under-hydroxylation of this residue leads to collagen structural abnormalities and results in moderate to lethal OI phenotype, despite the exact molecular mechanisms are still not completely clear. To shed light on these recessive forms, primary fibroblasts from OI patients with mutations in CRTAP (n = 3), P3H1 (n = 3), PPIB (n = 1) genes and from controls (n = 4) were investigated by a functional proteomic approach. Cytoskeleton and nucleoskeleton asset, protein fate, and metabolism were delineated as mainly affected. While western blot experiments confirmed altered expression of lamin A/C and cofilin-1, immunofluorescence analysis using antibody against lamin A/C and phalloidin showed an aberrant organization of nucleus and cytoskeleton. This is the first report describing an altered organization of intracellular structural proteins in recessive OI and pointing them as possible novel target for OI treatment. SIGNIFICANCE: OI is a prototype for skeletal dysplasias. It is a highly heterogeneous collagen-related disorder with dominant, recessive and X-linked transmission. There is no definitive cure for this disease, thus a better understanding of the molecular basis of its pathophysiology is expected to contribute in identifying potential targets to develop new treatments. Based on this concept, we performed a functional proteomic study to delineate affected molecular pathways in primary fibroblasts from recessive OI patients, carrying mutations in CRTAP (OI type VII), P3H1 (OI type VIII), and PPIB (OI type IX) genes. Our analyses demonstrated the occurrence of an altered cytoskeleton and, for the first time in OI, of nuclear lamina organization. Hence, cytoskeleton and nucleoskeleton components may be considered as novel drug targets for clinical management of the disease. Finally, according to our analyses, OI emerged to share similar deregulated pathways and molecular aberrances, as previously described, with other rare disorders caused by different genetic defects. Those aberrances may provide common pharmacological targets to support classical clinical approach in treating different diseases.